Cosmopolitical Alliances: Diplomatic Assemblages Between the Fields of Art and Science - Oliveira, Fernanda de Souza; Baio, Cesar (Farol, 2026)
This text aims to present an investigation into the potential contributions of visual artists to the fields of science and technology, drawing on the experiential account of an artist embedded in an Amazonian microbiology laboratory. The discussion is grounded in Isabelle Stengers’ cosmopolitical proposition, exploring the complex relationships involved in the exchange of knowledge between seemingly divergent fields—such as art and science. The study is based on the operative concepts of visual poetics and creative processes as an aesthetic force capable of forging cosmopolitical alliances; these alliances are articulated to expand disciplinary boundaries in knowledge production and leverage Amazonian cosmopolitics to reconfigure the boundaries between art, science, technology, and image.
Keywords: art; science; technology; image; visual poetics; cosmopolitics